Primary adenocarcinoma of duodenal bulb mimicking a pancreatic tumor: a case report - Eya Slama; S. Ben Hamida; S. Zaouga; H. Elloumi; I. Cheikh; A. G. Dahak; M. Missaoui; A. Chelibi; I. Ganzoui (Future Science OA)
Duodenal bulb adenocarcinoma is a rare malignancy of the gastrointestinal tract. This cancer often presents with an insidious onset, making it challenging to diagnose early. A noteworthy case-study involved a 56 year-old-woman complaining from epigastric transfixing pain, jaundice, and overall health decline. The initial diagnosis suspected was a pancreatic tumor. An abdominal CT scan however showed no abnormality in the pancreas but revealed on the other hand an irregular, non-stenosing, heterogeneous fibrous thickening of the lower aspect of the duodenal bulb. An EGD showed a congested infiltrated area in the post-bulbar region, and Pathological exam confirmed the diagnosis of a primary adenocarcinoma of the duodenal bulb. The purpose of this article is to present the case of a primary adenocarcinoma of duodenal bulb mimicking a pancreatic tumor: a rare presentation of a rare tumor itself and to present points differentiating these two neoplasms. Diagnosis relies on a comprehensive assessment involving clinical, radiological, endoscopic, and histologic features. Integration of advanced imaging modalities, such as CT/MRI, coupled with upper gastrointestinal endoscopy, is crucial for accurate evaluation.